Konstruksi Identitas Anak Muda di Youtube : Analisis Tekstual Konten “Kids Jaman Now” Pada Kanal YouTube Ecko Show dan Fikrifadlu - Syafrida Nurrachmi Febriyanti (LPPM Stikosa - AWS, 2020)
Youth is the most unique stage of development, full of dynamics and problems throughout human life. During this period there were fundamental changes from various aspects, including biological, cognitive and social. Young people in the digital era are trying to find their identity through social media, including YouTube. An interesting phenomenon is the emergence of viral content entitled “Kids Jaman Now”. This study aims to see how the identity of young people is constructed through the contents of